Reduced diaphragmatic function during term labor and its association with second stage of labor: an intrapartum ultrasound study - Liu, Chunfeng; Zhang, Shijie; Hong, Huilan; Chen, Yongjian; Lyu, Guorong (Frontiers in Physiology, 2026)
BackgroundTo investigate differences in diaphragmatic function between women undergoing term labor and healthy non-pregnant women, and to analyze the correlation between diaphragmatic function and duration of the second stage of labor. Key obstetric factors such as pre-labor BMI, estimated fetal weight, parity, oxytocin and epidural use were considered as potential confounders.MethodsThis prospective study was conducted at a tertiary perinatal center and included 94 women with term, singleton, cephalic pregnancies who underwent spontaneous vaginal delivery between December 2024 and April 2025. Diaphragmatic excursion and thickness were measured under different states during labor. A control group of 31 healthy non-pregnant women, matched for age, height, weight, and BMI, was also recruited. Differences in diaphragmatic excursion, thickness, and thickening ratio between the two groups were compared. Associations between diaphragmatic parameters and the duration of the second stage of labor were analyzed after adjusting the covariates selected by LASSO. It should be noted that over half of the controls had prior childbirths, which may modify baseline diaphragmatic morphology and introduce residual confounding.ResultsIn the labor group, tidal excursion and deep breath excursion were significantly lower than in controls (Effect size (95% CI) = −0.31 (−0.46, −0.16), P < 0.001, and −0.45 (−0.58, −0.30), P < 0.001). Deep inspiratory and Valsalva thickness were significantly lower in the labor group (−0.29 (−0.44, −0.11), P = 0.001, and −0.26 (−0.41, −0.10), P = 0.003). The deep breath and Valsalva thickness fractions were also reduced (−0.20 (−0.36, −0.04), P = 0.026, and −0.19 (−0.36, −0.01), P = 0.037). After LASSO regression, covariates including pre-labor BMI, parity and epidural use were selected. After adjusting for covariates (pre-labor BMI, parity and epidural), tidal expiratory and inspiratory thickness were positively correlated with the duration of the second stage of labor (β (95% CI) = 0.229 (3.286, 39.628), P = 0.021, and 0.201 (0.917, 32.855), P = 0.0380, whereas the deep breath thickness fraction was negatively correlated (−0.187 (−0.463, −0.005), P = 0.046).ConclusionWomen in term labor exhibited reduced diaphragmatic excursion and thinner diaphragmatic thickness under functional conditions compared with non-pregnant women. Observed associations indicated that tidal inspiratory thickness and deep breath thickness fraction were related to the duration of the second stage of labor. It should be noted that over half of the control participants had prior childbirths, which may influence baseline diaphragmatic morphology and introduce residual confounding. Given the observational design, causal inferences cannot be drawn.